Gemcitabine and split-dose paclitaxel or docetaxel in metastatic breast cancer: A randomised phase II study - Kei Siong Khoo (2018)
Purpose: The purpose was to evaluate the activity and toxicity of split-dose paclitaxel or docetaxel in combination with gemcitabine in patients with metastatic breast cancer (MBC) who had previously received anthracyclines. Patients and methods: A total of 210 patients were randomly assigned to one of three treatment arms: gemcitabine 1250 mg/m2Days 1 and 8 and paclitaxel 175 mg/m2as a 3-h infusion on Day 1 (GP1); gemcitabine 1000 mg/m2Days 1 and 8 and paclitaxel 100 mg/m2as a 1-h infusion on Days 1 and 8 (GP2); gemcitabine 1000 mg/m2Days 1 and 8 and docetaxel 40 mg/m2as a 1-h infusion on Days 1 and 8 (GD). Cycles were repeated every 3 weeks. Results: For the 204 patients evaluable for response assessment, the response rates were 48.6% for GP1, 52.2% for GP2, and 52.3% for GD. Median response duration, time to treatment failure, and time to progression (TTP) were similar in each arm. Median TTP for GP1, GP2 and GD was 7.5, 7.0 and 7.4 months, respectively. For the 208 patients evaluable for safety, the most common grade 3/4 toxicity for each regimen was neutropaenia, with 64%, 57%, and 68% for GP1, GP2, and GD, respectively. Grade 4 neutropaenia, grade 3/4 anaemia, febrile neutropaenia, and diarrhoea were more common in the docetaxel arm, as was the use of intravenous antibiotics and blood transfusions. Conclusion: The study confirmed the high activity of gemcitabine-taxane combinations in MBC. Split-dose paclitaxel had similar activity and toxicity to the 3-weekly administration. The split-dose docetaxel regimen had similar activity to the paclitaxel combinations though associated with higher toxicity. © 2006 Elsevier Ltd. All rights reserved.